Resilience of Tourists’ Repurchase Intention during the COVID-19 Pandemic: The Shared Accommodation Sector - Yan Wang (MDPI AG, 2021)
The economy has suffered unprecedentedly during the COVID-19 pandemic, including the shared accommodation sector. This study aims to discover the pandemic consumer behavior model for the recovery of the sector as well as investigate the economic resilience of tourists’ behavior to prevent and control the normalized pandemic. Most of the resilience literature discussed the level of economic and industry revitalization. There are relatively few studies on the individual level of tourists’ resilience. Therefore, we applied the adjusted theory of planned behavior with pandemic-related intrinsic factors to construct the research model, which is analyzed by the SEM approach. The results show that perceived risk affects tourists’ perceived value, trust, and behavioral attitude when repurchasing shared accommodation during the pandemic. The repurchase intention is indirectly affected by the behavioral attitude and perceived value. We concluded that the perceived risk of the pandemic could be resilient with respect to the perceived value, trust, and behavioral attitude for the repurchase intention of the shared accommodation for the sector to recover.